(1115) beliefs, practices, environment and services affecting the survival, growth and development of young(115) Egyptian children: a comparative study in tow Egyptian governorates(pI) المعتقدات والممارسات والبيئة والخدمات التي تؤثر على بقاء ونمو وتطور الأطفال المصريين الصغار (115): دراسة مقارنة في محافظتين مصريتين (الجزء الاول) - hassouna, W. A. (the institute of national planning, 2018)

(untitled)
two main institutions which provide direct care to the pre-school age group are the MCH centers supervised by the ministry of health and day care centers supervised by the ministry of social affairs and hence these are given special emphasis in this study.